2020
DOI: 10.3389/fpls.2020.00924
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Synthesis of Pharmaceutically Active Abietane Diterpenes in S. sclarea Hairy Roots by Engineering the GGPPS and CPPS Genes

Abstract: Abietane diterpenoids (ADs), synthesized in the roots of different Salvia species, such as aethiopinone, 1-oxoaethiopinone, salvipisone, and ferruginol, have a variety of known biological activities. We have shown that aethiopinone has promising cytotoxic activity against several human tumor cell lines, including the breast adenocarcinoma MCF7, HeLa, epithelial carcinoma, prostate adenocarcinoma PC3, and human melanoma A375. The low content of these compounds in natural sources, and the limited possibility to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 76 publications
(106 reference statements)
1
13
0
Order By: Relevance
“…This was an important observation as these are the key catalytic enzymes responsible for ent-diterpenoid synthesis and are highly conserved in all terpenoid-synthesizing organisms [52]. Thus, enhanced diterpene synthesis and accumulation have been achieved by overexpressing the CPS or GGPPS gene in Salvia species [52,53] and tobacco [54]. Similarly, Jassbi et al [55] demonstrated that the silencing of GGPPS disrupted the synthesis of 17-hydroxygeranyllinalool diterpenoid glycosides, together with the increased susceptibility to tobacco hornworm.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This was an important observation as these are the key catalytic enzymes responsible for ent-diterpenoid synthesis and are highly conserved in all terpenoid-synthesizing organisms [52]. Thus, enhanced diterpene synthesis and accumulation have been achieved by overexpressing the CPS or GGPPS gene in Salvia species [52,53] and tobacco [54]. Similarly, Jassbi et al [55] demonstrated that the silencing of GGPPS disrupted the synthesis of 17-hydroxygeranyllinalool diterpenoid glycosides, together with the increased susceptibility to tobacco hornworm.…”
Section: Discussionmentioning
confidence: 98%
“…Even more striking was the upregulation of genes encoding GGPPS and CPS, by NO 3 − feeding. This was an important observation as these are the key catalytic enzymes responsible for ent-diterpenoid synthesis and are highly conserved in all terpenoid-synthesizing organisms [52]. Thus, enhanced diterpene synthesis and accumulation have been achieved by overexpressing the CPS or GGPPS gene in Salvia species [52,53] and tobacco [54].…”
Section: Discussionmentioning
confidence: 98%
“…For example, FPPS overexpression increased the production of ganoderic acid [ 42 ]. A high number of monoterpenes was produced by overexpression of peppermint ( Mentha × piperita ) GPPS.SSU in transgenic tobacco plants [ 43 ] and the content of abietane diterpenes in Salvia sclarea L. hairy roots was increased by engineering the GGPPS and CPPS [ 44 ]. In this research, six DEGs encoding IPTS were identified, including one GPPS , two FPPS , and three GGPPS .…”
Section: Discussionmentioning
confidence: 99%
“…of the terpene biosynthetic pathway have recently been successfully overexpressed in Salvia spp. to increase terpenoid yield ( Vaccaro et al, 2020 ; Shi et al, 2016 ; Kai et al, 2011 ). This is a feasible strategy for enhancing the production of natural products by manipulating a number of biosynthetic genes at regulatory points.…”
Section: Discussionmentioning
confidence: 99%